Describing the impact of the COVID‐19 pandemic on alcohol‐induced blackout tweets. (6th October 2020) - Ward, Rose Marie; Riordan, Benjamin C.; Merrill, Jennifer E.; Raubenheimer, Jacques
Abstract: Introduction and Aims: COVID‐19, considered a pandemic by the World Health Organization, overwhelmed hospitals in the USA. In parallel to the growing pandemic, alcohol sales grew in the USA, with people stockpiling alcohol. Alcohol‐induced blackouts are one particularly concerning consequence of heavy drinking, and the extent to which blackout prevalence may change in the context of a pandemic is unknown. The purpose of the current study is to describe the prevalence of publicly available tweets in the USA referencing alcohol‐induced blackouts prior to and during the COVID‐19 outbreak. Design and Methods: We used Crimson Hexagon's ForSight tool to access all original English tweets written in the USA that referenced alcohol‐related blackouts in 2019 and 2020. Using infoveillance methods, we tracked changes in the number and proportion of tweets about blackouts. Results: More alcohol‐related blackout tweets were written between 13 March and 24 April in 2020 than 2019. In addition, a greater proportion of all tweets referenced blackouts in 2020 than in 2019. In the period prior to the 'stay at home' orders (January to mid‐March), the proportion of blackout tweets were higher in 2020 than 2019. Discussion and Conclusion: Our findings demonstrate that references to high‐risk drinking persist during the pandemic despite restrictions on large social gatherings. Given that the internet is a common source of information for COVID‐19, the frequent posting about blackouts during this period might normalise the behaviour. This is concerning because alcohol use increases susceptibility to COVID‐19, and alcohol‐related mortality can further tax hospital resources.